PENGEMBANGAN MEDIA MULTIFORM INSTRUKSIONAL BERBASIS AJARAN AGAMA HINDU - Putra Sentosa, Rai Bagus (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The improvement of understanding and knowledge of learning about Hinduism is very important to a teacher to maximize the result, and students to be able to understand the knowledge of learning the religion. Inside the Veda, there is mentioned about the responsibility and the obligation of a teacher that is born with the dawn and gives knowledge for those who are lacking. Through some methods to improve the interest and understanding of the students and paper-based learning media with the concept of Hindu that are commoditized with software-based application to draw the learning interest of the students such as forming learning media, using Tri Datu thread, which people currently use used but not so sure about the philosophical meaning that is full of meaning of Hindu. This is really wonderful if we relate the concept of Tri Murti with the responsibility and the obligation of a teacher. Through the students who study in Elementary School to explain and give information that can be claimed as correct information based on the existed history where there is many concept in Hindu that has many meanings.